THE DIFFERENCE BLOOD CORTISOL LEVEL BETWEEN MALE AND FEMALE ON WORKERS EXPOSED BY CONTINOUS NOISE - Sumardiyono Sumardiyono (Journal of Vocational Health Studies)
Background: Noise is a dangerous stressor in the workplace. One industry that has a high-risk noise intensity is the textile industry, which can have a stressful impact on workers. Stress can be shown by increased blood cortisol levels. Purpose: This study aimed to determine differences on blood cortisol levels of male and female workers exposed to continuous noise in the textile industry. Method: This study used analytic observational with cross sectional design. The research population is the worker weaving PT. Iskandar Indah printing Textile Surakarta amounts to 565 people. The sampling technique used purposive random sampling. Inclusion criteria: the work period is at least 1 year and age is at least 20 years. The sample obtained by using the calculation formula of mean difference is the number of samples per group of 20 people. Statistical test used Independent Samples T Test at the 0.05 level of significance. Results: The results showed the noise intensity in the weaving section between 93-105 dBA. Male group cortisol levels were 14.4±3.7 µg/dL and the female group were 11.8±3.7 µg/dL. The result of Independent Samples T Test statistic is shown significant test result (t=2,241; p=0,031). Conclusion: There is a difference in blood cortisol levels between male and female workers exposed to continuous noise in the textile industry. The conclusion of this study is that the level of stress due to exposure to continuous noise is a group of male workers is higher than female workers.